Perubahan Populasi Protozoa dan Alga Dominan pada Air Genangan Tanah Padi Sawah yang Diberi Bokashi Berkelanjutan - Niswati, Ainin; Dermiyati, .; Arif, Mas Achmad Syamsul (JOURNAL OF TROPICAL SOILS, 2008)
Protozoa and alga play important roles in biogeochemical nutrient cycles in freshwater environment, especially in the paddy fields.  The changes from the conventional technologies to organic technologies will change the communities structures of organisms lived in the paddy fields environment.  The fields experiment was conducted to study the population dynamic of protozoa and algae dominant inhabited in  the floodwater of the paddy fields subjected by continues ‘bokashi’ application.  The results showed that protozoa and algae inhabited in the paddy fields in present study were dominated by Euglena, Pleodorina, Volvox, and Diatom. The continued application of  bokashi for 4 years significantly increased the total population of protozoa and algae, however, the significantly effect was obtained in the population of Volvox only.  The population of protozoa and algae were affected by the time of flooding of paddy fields where it increases exponentially at the 20 and 30 days after flooding and stable after that, ecxept for Euglena where it increases little by little with time of flooding.